Clinical Outcomes After Cell-Seeded Autologous Chondrocyte Implantation of the Knee: When Can Success or Failure Be Predicted?. (January 2014) - Pestka, Jan M.; Bode, Gerrit; Salzmann, Gian; Steinwachs, Mathias; Schmal, Hagen; Südkamp, Norbert P.; Niemeyer, Philipp
Background: Autologous chondrocyte implantation (ACI) has been associated with satisfying results. Still, it remains unclear when success or failure after ACI can be estimated. Purpose: To evaluate the clinical outcomes of cell-seeded collagen matrix–supported ACI (ACI-Cs) for the treatment of cartilage defects of the knee at 36 months and to determine a time point after ACI-Cs at which success or failure can be estimated. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 80 patients with isolated full-thickness cartilage defects of the knee joint treated with ACI-Cs were prospectively assessed before surgery as well as postoperatively by use of the International Knee Documentation Committee (IKDC) score and Lysholm knee score. Results: Preoperative IKDC and Lysholm scores increased from 49.6 and 59.5, respectively, to 79.1 and 83.5, respectively, at 36 months. Only half the patients (46.6%) with poor IKDC scores (ie, <70) at 6 months postoperatively showed continued poor or fair scores at 36 months' follow-up. The probability of poor scores at 36 months after surgery further increased to 0.61 and 0.81, respectively, when scores were persistent at 12 and 24 months. All 3 patients (100%) with good IKDC scores (ie, 81-90) at 6 months after surgery showed constant or even improved scores at 36 months' follow-up. Ninety-one percent of patients with good and excellent scores at 12 months and 83% of patients with good and excellent scores at 24 months (a total of 23 and 37 patients, respectively) were able to maintain these scores at 36 months' follow-up. Similar results were obtained for the Lysholm score. Conclusion: With regard to the improvements in functional outcomes after ACI-Cs at 36 months after surgery, the technique described here appears to lead to satisfying and stable clinical results. This study helps the treating physician to predict the likeliness of further clinical improvements or constant unsatisfactory results after ACI. In patients with good/excellent scores shortly after surgery, deterioration of the knee's condition is rarely found. For patients with poor and fair postoperative scores, clinical outcomes are more difficult to predict, especially during the first year after the procedure.